Understanding the Ion Transport Behavior across Nanofluidic Membranes in Response to the Charge Variations. (12th February 2021) - Hou, Linxiao; Xian, Weipeng; Bing, Shaosuo; Song, Yanpei; Sun, Qi; Zhang, Lin; Ma, Shengqian
Abstract: Biological pores regulate the cellular traffic of a diverse collection of molecules, often with extremely high selectivity. Given the ubiquity of charge‐based separation in nature, understanding the link between the charged functionalities and the ion transport activities is essential for designing delicate separations, with the correlation being comparatively underdeveloped. Herein, the effect of charge density from the impact of pore structure is decoupled using a multivariate strategy for the construction of covalent organic framework‐based membranes. How the density of charged sites in the nanofluidic membranes affect the ion transport activity with particular emphasis on Li + and Mg 2+ ions, relevant to the challenge of salt‐lake lithium mining is systematically investigated. Systematic control of the charge distribution produces membranes with numerous advantages, overcoming the long‐term challenge of Li + /Mg 2+ separation. The top membrane exhibits an outstanding equilibrium selectivity for Li + over Mg 2+ and operational stability under diffusion dialysis and electrodialysis conditions (Li + /Mg 2+ up to 500), qualifying it as a potential candidate for lithium extraction. It is anticipated that the developed nanofluidic membrane platform can be further leveraged to tackle other challenges in controlled separation processes. Abstract : The role of charged sites in the nanofluidic membranes on ion transport behavior is delineated by comparing the transmembrane kinetics of Li + and Mg 2+ ions using isoreticular covalent organic frameworks with the same pore size yet different compositions.